(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Sustainable development is longer that meet the needs of the present generation without compromising the ability of future generations to meet their own needs as it seeks to harmonize economic, social, Why research aims to check the availability of a proposed program takes into account the evidence and scrutiny of financial commitment and performance audit in accordance with the dimensions of sustainable development (economic, environmental, social and institutional) to measure the extent of the province on the needs of current and future generations, The problem with research that there is no audit program ensures the audit of financial statements, commitment and performance of health services in order to achieve sustainable development. Search based on the premise that health institutions scrutiny leads to the ability to maintain the current and future generations, The existence of audit program, both in the Department of Internal Audit of the Court of Federal Financial Supervisory includes indicators and targets and principles of the sustainable development of health institutions to ensure the achievement dimensions of sustainable development according to the types of audit (financial commitment and performance). The study came out a set of recommendations from, the study of the existence of audit program includes scrutiny of health institutions to ensure financial matters, commitment and performance to achieve dimensions of sustainable development (economic, social, environmental and institutional), To show the extent of the institution’s commitment to the preparation of reports on sustainable development and knowledge of the extent of its contribution to the preservation of the environment from pollution, to reduce the spread of diseases and control them, and the need to adopt health and sustainable development indicators to measure progress, in the provision of health services and stand on the obstacles to achieving development and get closer to achieving development goals when developing plans and strategies and financial resources.